Temporal association between the isolation of Sabin-related poliovirus vaccine strains and the Guillain-Barré syndrome - F. Friedrich; A. M. B. Filippis; H. G. Schatzmayr (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
Thirty eight paralysis cases classified as Guillain-Barré syndrome (GBS) in Brazil were analysed. In all these cases Sabin-related poliovirus vaccine strains were isolated. In most of the cases the last vaccine dose was given months or years before the onset of GBS, suggesting a persistent infection or the transmission of the Sabin-related strains to the patients. The isolation of Sabin-related strains from GBS cases some days or weeks after the onset of the disease, demonstrated a temporal association between the isolation of the strains and the disease. Although the isolates from the GBS cases may not be the etiological agent of the disease, this study strongly indicates that infections caused by Sabin-related vaccine strains can trigger the GBS in certain cases.